2015
DOI: 10.1093/femsec/fiv011
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals adaptations to a cold-adapted lifestyle in a low-temperature acid mine drainage stream

Abstract: An acid mine drainage (pH 2.5-2.7) stream biofilm situated 250 m below ground in the low-temperature (6-10°C) Kristineberg mine, northern Sweden, contained a microbial community equipped for growth at low temperature and acidic pH. Metagenomic sequencing of the biofilm and planktonic fractions identified the most abundant microorganism to be similar to the psychrotolerant acidophile, Acidithiobacillus ferrivorans. In addition, metagenome contigs were most similar to other Acidithiobacillus species, an Acidobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 88 publications
0
55
1
1
Order By: Relevance
“…were found to be predominant at the late oxidation stage, which was usually characterized by low pH (<3.0) and a high concentration of metals [47,49,50], revealing their favorable adaptation of harsh environmental conditions and indispensability in such ecosystems [51]. Metagenomic as well as transcriptomic analyses deciphered significant variations in microbial community function [27,52,53].…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…were found to be predominant at the late oxidation stage, which was usually characterized by low pH (<3.0) and a high concentration of metals [47,49,50], revealing their favorable adaptation of harsh environmental conditions and indispensability in such ecosystems [51]. Metagenomic as well as transcriptomic analyses deciphered significant variations in microbial community function [27,52,53].…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
“…In summary, microbial-mediated AMD generation results in a low alpha-diversity of microbial community at the late stage. [27,52,53]. For example, previous metagenomics study of tailings acidification showed that the sulfur oxidation was mainly performed by Thiobacillus at the early stage and by Acidithiobacillus at the late stage [50].…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
“…In addition, a metagenomic study identified potential adaptations of acidophiles (including an At. ferrivorans -like population) to low temperatures in an acid mine drainage stream community in northern Sweden (Liljeqvist et al 2015). These adaptations include CSPs, several pathways for the production of compatible solutes, growth as a biofilm, and an anti-freeze protein.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aims to elucidate the At. ferrivorans transcriptional response to cultivation at 8 °C, a temperature relevant in low temperature mining environments (Liljeqvist et al 2015), compared 20 °C, a temperature near to where it shows the highest growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the dominance of bacteria in the biofilms obtained, these results suggest that the bacteria present at Site B and/or Site C (which was not evaluated for its proportions of eukaryotes, archaea, and bacteria) are the most likely candidates for the removal of aqueous Cu from the water column, if bioremediation was occurring. A low proportion of eukaryotes in an acidic, alkaline, and/or metals-rich environment does not appear to be unusual, although studies of these environments often focus on microbial community structures and thus the eukaryotic proportion is not evaluated or reported (Bier et al, 2014;Tsitko et al, 2014;Liljeqvist et al, 2015). It is possible that the biofilm collection period of 18 days may have affected the final composition of the communities through succession limitations (i.e., limited colonization of eukaryotes).…”
Section: Discussionmentioning
confidence: 99%